The Digital communication network transformation: Scopus-based analysis of technological progress and future challenges - Indriyani, Nurul Aeni; latupeirissa, jonathan jacob paul (Jurnal Studi Komunikasi, 2026)
The profound and ongoing transformation of digital communication networks is driven by advancements from foundational internet infrastructure like ARPANET to modern interactive platforms and sophisticated AI. This transformation has fundamentally reshaped societal structures and human interaction. It compels a critical reconsideration of established norms. While extensive research exists on individual aspects of this shift, a comprehensive and systematic analysis that synthesises its multifaceted impact on social structures, individual experiences, and emergent challenges remains crucial. Therefore, this Scopus-based systematic literature review aims to identify and categorise key technological advancements and their evolution. It thoroughly analyses the societal, political, and ethical challenges and risks arising from this transformation and synthesises its impact on social structures and individual experiences. The qualitative research design employed PRISMA guidelines, refined through abstract and full-text screening, which yielded 46 articles for in-depth analysis. Key findings indicate a dynamic interplay where technological progress, including advanced AI integration, generates digital anomie, algorithmic manipulation, and regulatory gaps. These factors fundamentally alter communication culture and require a re-evaluation of truth criteria and social stratification. In conclusion, the move towards hybrid, AI-driven communication systems presents complex dilemmas. Future research should focus on developing robust regulatory frameworks for AI, enhancing media literacy against algorithmic influence, and exploring interdisciplinary approaches to mitigate societal fragmentation and ethical challenges.